Porcelain and manufacturing method of porcelain

A ceramic composition with controlled silicon dioxide, aluminum oxide, calcium oxide, alkali metal oxide, and diphosphorus pentoxide ratios stabilizes firing deformation, addressing bone china manufacturing challenges by allowing stable production across broader temperature ranges and eliminating unnecessary firing processes.

JP2025044327APending Publication Date: 2025-04-02SAGA PREFECTURE +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023151831
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing bone china manufacturing processes face significant firing deformation issues due to narrow temperature ranges and temperature variations in firing furnaces, leading to reduced yield and unstable product shapes, especially when incorporating high amounts of bone ash.

Method used

A ceramic composition comprising specific ratios of silicon dioxide, aluminum oxide, calcium oxide, alkali metal oxide, and diphosphorus pentoxide, with a reduced feldspar content, is used to stabilize the firing deformation by crystallizing cristobalite from the glass matrix, allowing firing within a broader temperature range without substantial deformation.

Benefits of technology

The solution suppresses firing deformation changes by 40% or less across a 50°C temperature range, enabling stable porcelain production with reduced temperature sensitivity and eliminating the need for double firing and glaze firing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044327000001_ABST
    Figure 2025044327000001_ABST
Patent Text Reader

Abstract

To provide a porcelain having suppressed difference (rate of change) of firing deformation amount based on temperature differences in a temperature zone in a calcination process.SOLUTION: A porcelain comprises a main raw material composition that includes, excluding an inevitable contaminant, on an oxide basis, 44 mass% or more and 60 mass% or less of silicon dioxide, 10 mass% or more and 15 mass% or less of aluminum oxide, 10 mass% or more and 20 mass% or less of calcium oxide, 0.3 mass% or more and 1.3 mass% or less of an alkali metal oxide, and 14 mass% or more and 24 mass% or less of diphosphorus pentaoxide.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to porcelain in which the amount of deformation during firing is suppressed even when the porcelain material contains 14% by mass or more of diphosphorus pentoxide (equivalent to 25% by mass or more of bone ash), and to a method for producing the same. [Background technology]

[0002] For hard porcelain, a decorative technique called underglaze is used, in which a picture is painted between the glaze layer and the base. To apply underglaze, the porcelain material is first bisque fired at a temperature of 700 to 1000°C, the paint is applied to the water-absorbent base, and the glaze is applied, and the product is then fired at a temperature of 1200 to 1400°C. In this manufacturing process, the glaze softens on the surface during firing, so if a mold called a saya is used to support the firing deformation of the base, the glaze and the saya will fuse together and the product cannot be obtained, so a saya is not used.

[0003] Bone china, as typified by bone china, is excellent in terms of whiteness, translucency, and strength, and is widely used for luxury tableware. Bone china is also called soft porcelain, and has the characteristic that it contains a large amount of glass when porcelainized, so it rapidly deforms when fired after porcelainization. Porcelainization refers to the state in which the porcelain raw material is sintered by firing and absorbs almost no water.

[0004] In the manufacture of bone china, first the piece is baked at a temperature of 1200 to 1400°C, and then glaze is applied and the piece is baked at a temperature of about 1100°C where deformation during firing does not occur (see Patent Document 1). By utilizing the magnitude of deformation during firing, the base material can be deformed along the sheath during baking, making it possible to manufacture products with extremely high precision. On the other hand, in the case of bone china, where deformation during firing rapidly increases due to overfiring, even slight differences in the firing temperature can significantly change the product shape, resulting in reduced yields. For this reason, there was room for improvement in the composition of the porcelain and the manufacturing process for porcelain in conventional bone china.

[0005] Patent Document 2 proposes a method for producing bone china by the steps of bisque firing, glazing, and firing in order to simplify the manufacturing process. Patent Document 3 also proposes a method for producing bone china by the steps of bisque firing, glazing, and firing. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-121850 A [Patent Document 2] Japanese Patent Application Publication No. 53-052514 [Patent Document 3] JP 2016-79074 A Summary of the Invention [Problem to be solved by the invention]

[0007] In the prior art described in Patent Document 2, a green body is obtained by mixing 7% or more of feldspar, which is a flux, in the raw materials. However, with such a mixture, there is a problem that firing deformation progresses significantly as the firing temperature rises during firing. In addition, the firing temperature range during firing is from 1230°C to 1270°C, and this temperature range is narrow at 40°C. Therefore, when there is a temperature distribution in the firing furnace and there is a space outside this temperature range in the furnace, there is a problem that products with large firing deformation are produced, and the yield rate decreases.

[0008] In the prior art described in Patent Document 3, the firing temperature is specified to be in the range of 1200°C to 1250°C. In order to maintain this temperature range, a firing furnace with a very small temperature difference inside the furnace must be used, and the firing temperature must be strictly controlled in order to produce with a good yield. In addition, the temperature difference inside the furnace of kilns used for mass production of ceramics is generally 40°C or more. [Means for solving the problem]

[0009] The present invention is intended to solve the above-mentioned problems, and aims to provide porcelain in which, when a firing process is carried out in a specified temperature range, the difference (rate of change) in the amount of firing deformation due to different temperature differences within that temperature range is suppressed, and a method for manufacturing such porcelain.

[0010] For this reason, the ceramic according to the present invention can be made of a main raw material composition that includes, on an oxide basis, excluding unavoidable impurities, 44% by mass or more and 60% by mass or less of silicon dioxide, 10% by mass or more and 15% by mass or less of aluminum oxide, 10% by mass or more and 20% by mass or less of calcium oxide, 0.3% by mass or more and 1.3% by mass or less of alkali metal oxide, and 14% by mass or more and 24% by mass or less of diphosphorus pentoxide.

[0011] Furthermore, the ceramic according to the present invention may contain, for example, a secondary raw material composition other than the main raw material composition.

[0012] Moreover, in the ceramic according to the present invention, the main raw material composition may account for 95 mass % or more.

[0013] Furthermore, the porcelain according to the present invention may have, for example, cristobalite as a crystal phase.

[0014] Furthermore, the ceramic according to the present invention can have, for example, a first peak of cristobalite at 2θ=21.7° in an X-ray diffraction pattern that is greater than a second peak of α-quartz at 2θ=20.7°.

[0015] In the ceramic according to the present invention, for example, the blending ratio of feldspar as a raw material of the main raw material composition can be less than 7 mass %.

[0016] Furthermore, the method for producing porcelain according to the present invention can include, for example, a preparation step of preparing clay made from a main raw material composition containing, on an oxide basis, excluding unavoidable impurities, 44% by mass or more and 60% by mass or less of silicon dioxide, 10% by mass or more and 15% by mass or less of aluminum oxide, 10% by mass or more and 20% by mass or less of calcium oxide, 0.3% by mass or more and 1.3% by mass or less of alkali metal oxide, and 14% by mass or more and 24% by mass or less of diphosphorus pentoxide, a molding step of molding the clay prepared in the preparation step into a molded body, and a firing step of firing the molded body molded in the molding step at 1150°C or more and 1330°C or less.

[0017] Furthermore, the method for producing ceramics according to the present invention may have a secondary raw material composition other than the main raw material composition.

[0018] In the method for producing ceramics according to the present invention, the main raw material composition may be 95% by mass or more.

[0019] In addition, the method for producing porcelain according to the present invention includes the steps of: The main raw material composition may contain feldspar in an amount of less than 7 mass %.

[0020] Furthermore, in the method for manufacturing porcelain according to the present invention, when the amount of firing deformation when fired at a first firing temperature T1 of 1150°C or higher and 1330°C or lower is D1, and the amount of firing deformation when fired at a second firing temperature T2 of 1150°C or higher and 1330°C or lower is D2 (where T2-T1=50°C), the rate of change in the amount of firing deformation calculated by {(D2-D1) / D1}×100 can be 40% or less. Effect of the Invention

[0021] The porcelain according to the present invention is made of a main raw material composition having an appropriate compositional ratio, and it is possible to provide a porcelain in which the difference (rate of change) in the amount of firing deformation due to different temperature differences within a temperature range during the firing process is suppressed.

[0022] Furthermore, according to the porcelain manufacturing method of the present invention, after porcelainization at a temperature of 1150°C or higher and 1280°C or lower, even if the firing temperature is increased by 50°C or more, the amount of firing deformation hardly increases, making it possible to manufacture porcelain products with stable shapes.

[0023] The present invention also provides a porcelain material that contains 25% or more bone ash and has low temperature dependence of firing deformation.The present invention also provides a method for producing porcelain that contains 25% or more bone ash and does not require the processes of double firing and glaze firing. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a side view illustrating the sample support table (2) used in firing the ceramic of the present invention and the state in which the plate-shaped sample (1) is placed. [Diagram 2] FIG. 1 is a diagram illustrating the measurement points of firing deformation (3). [Diagram 3] FIG. 2 is an X-ray diffraction diagram of the porcelain obtained by firing Example 1 at a temperature of 1200° C. [Figure 4] FIG. 2 is an X-ray diffraction diagram of the porcelain obtained by firing Example 1 at a temperature of 1250° C. [Diagram 5] FIG. 2 is an X-ray diffraction diagram of the porcelain obtained by firing Comparative Example 1 at a temperature of 1200° C. [Figure 6] FIG. 2 is an X-ray diffraction diagram of the porcelain obtained by firing Comparative Example 1 at a temperature of 1250° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The definitions of the terms used in this specification are explained below. In this specification, the mixture of the raw materials before firing is called "clay" or "porcelain material". Such "clay" or "porcelain material" can include a main raw material composition that forms the skeleton of the porcelain, and a secondary raw material composition that is a composition other than the main raw material composition and is used, for example, to color the porcelain. However, the secondary raw material composition is not essential, and the secondary raw material composition does not have to be included in the "clay" or "porcelain material".

[0026] The above-mentioned "china clay" or "porcelain material" is fired in a firing furnace and cooled to room temperature to become "porcelain." The manufacturing process in the "porcelain manufacturing method" can include a process of mixing the various raw materials and a process of firing the "china clay" or "porcelain material."

[0027] In the "porcelain" state, the ratio of the main raw material composition to the auxiliary raw material composition is preferably 95% by mass or more of the former composition and less than 5% by mass of the latter composition. More preferably, the ratio is 98% by mass or more of the former composition and less than 2% by mass of the latter composition. If the ratio of the former composition is less than 95% by mass, the function as the skeleton of the porcelain is lost.

[0028] In addition, in this specification, "porcelainization" refers to a state in which, when the above-mentioned "china clay" or "porcelain material" is fired in a firing furnace, sintering progresses and the fired product no longer absorbs water.

[0029] In addition, in this specification, "bone china" refers to china in which bone ash is 25% by mass or more of the raw material. Note that for the china according to the present invention, it is not essential that bone ash is 25% by mass or more of the raw material, and the phosphorus source does not have to be limited to bone ash as long as the diphosphorus pentoxide contained in the main raw material composition is 14% by mass or more.

[0030] In this specification, terms such as "first peak" and "second peak" are used in the X-ray diffraction pattern obtained by the X-ray diffraction apparatus used to analyze the above-mentioned "porcelain." The meaning of the terms "first" and "second" in these peaks is defined below. When an analysis is performed using an X-ray diffraction apparatus, multiple peaks due to a certain crystal phase may be obtained. Among these multiple peaks, the largest one will be referred to as "first," "second," "third," ...

[0031] Next, the present invention will be described in detail. In bone china containing 25% or more by mass of bone ash, quartz particles, which are silicon dioxide (SiO2) crystals and serve as aggregates that maintain the shape of the porcelain material during firing, are easily melted into the glass matrix that is generated during firing, and as the aggregate decreases during firing, firing deformation progresses rapidly after porcelainization.

[0032] Therefore, in the present invention, we considered crystallizing cristobalite, a silicon dioxide crystal that is stable at high temperatures, from a glass matrix as an aggregate to replace quartz particles in accordance with the melting of quartz particles during firing of the porcelain material, and adjusted the composition of the porcelain material.

[0033] The glass matrix can be considered to be amorphous silicon dioxide in which alkali metals (Na, K) that melt and roast silicon dioxide, aluminum, phosphorus, etc. are dispersed. Since it is inevitable for bone porcelain materials to contain a considerable amount of phosphorus, when adjusting the porcelain material in the present invention, adjustments were made to suppress the alkali metals (Na, K) and aluminum. In the porcelain material used in the present invention, the melting power of silicon dioxide is suppressed in this way, so that cristobalite is crystallized from the glass matrix.

[0034] As described above, in the porcelain material that can be used in the present invention, the proportion of alkali metal oxides (Na2O, K2O) and aluminum oxide (Al2O3) is reduced from the composition of general bone porcelain materials to reduce the proportion of silicon dioxide that can exist stably in the glass matrix, so that cristobalite crystals are crystallized from the excess silicon dioxide in the glass matrix due to the melting of quartz particles. Furthermore, after reducing the proportions of alkali metal oxides and aluminum oxide, the mixing ratios of these components were also carefully studied.

[0035] As a result of careful consideration, the inventors have found that it is preferable for the ceramic according to the present invention to be made from a main raw material composition containing, on an oxide basis, excluding unavoidable impurities, 44% by mass or more and 60% by mass or less of silicon dioxide (SiO2), 10% by mass or more and 15% by mass or less of aluminum oxide (Al2O3), 10% by mass or more and 20% by mass or less of calcium oxide (CaO), 0.3% by mass or more and 1.3% by mass or less of alkali metal oxides (Na2O, K2O), and 14% by mass or more and 24% by mass or less of diphosphorus pentoxide (P2O5).

[0036] The ceramic according to the present invention may contain an auxiliary raw material composition in addition to the main raw material composition as described above. However, when such an auxiliary raw material composition is contained in the ceramic, the main raw material composition is preferably contained in an amount of 95 mass% or more.

[0037] In the porcelain according to the present invention, cristobalite crystals, which are stable at high temperatures, are crystallized from the glass matrix as an aggregate in place of quartz particles and are present in the porcelain. Furthermore, in the porcelain according to the present invention, the first peak of cristobalite at 2θ=21.7° in the X-ray diffraction pattern is larger than the second peak of α-quartz at 2θ=20.7°.

[0038] In addition, in the ceramic according to the present invention, the blending ratio of feldspar as a raw material of the main raw material composition is less than 7 mass %.

[0039] In addition, the method for producing porcelain according to the present invention includes at least a preparation step of preparing clay consisting of the above-mentioned main raw material composition, a molding step of molding the clay prepared in the preparation step into a molded body, and a firing step of firing the molded body formed in the molding step at a temperature of 1150°C or higher and 1330°C or lower.

[0040] In addition, the method for producing ceramics according to the present invention may contain an auxiliary raw material composition in addition to the main raw material composition described above. However, when such an auxiliary raw material composition is contained in the ceramics, the main raw material composition is preferably 95 mass% or more.

[0041] In the method for producing ceramics according to the present invention, the main raw material composition contains feldspar at a mixing ratio of less than 7 mass %.

[0042] Furthermore, in the method for manufacturing porcelain of the present invention, when the amount of firing deformation when fired at a first firing temperature T1 of 1150°C or higher and 1330°C or lower is D1, and the amount of firing deformation when fired at a second firing temperature T2 of 1150°C or higher and 1330°C or lower is D2 (where T2-T1=50°C), the rate of change in the amount of firing deformation calculated by {(D2-D1) / D1}×100 is 40% or less.

[0043] Next, the ceramic according to the present invention and the main raw material composition used in the method for producing the ceramic according to the present invention will be described.

[0044] Silicon dioxide, which is the main component of the porcelain material used in the present invention, may be derived from porcelain stone such as silica stone, silica, Amakusa porcelain stone, or feldspar raw materials, but may also be supplied from raw materials such as clay minerals, kaolin minerals, and wollastonite. Silicon dioxide is preferably contained in an amount of 44% by mass or more and 60% by mass or less. The content of silicon dioxide is preferably 45% by mass or more and 58% by mass or less, and more preferably 47% by mass or more and 57% by mass or less, based on the oxide standard composition. If the silicon dioxide content is less than 44% by mass, the ratio of silicon dioxide to the ratio of alkaline earth metal oxides and diphosphorus pentoxide decreases, so that the formation of a glass matrix is ​​insufficient and the possibility of not porcelainizing increases. On the other hand, if the silicon dioxide content exceeds 60% by mass, the amount of the glass matrix increases, and firing deformation becomes rapidly large as the temperature rises after porcelainization.

[0045] The aluminum oxide may be derived from clay minerals, kaolin minerals, pottery stones such as Amakusa pottery stones, or feldspar materials. A part of the aluminum oxide melts in the glass and contributes to the formation of the glass matrix as a modified oxide. The aluminum oxide in the glass matrix stabilizes silicon dioxide as a glass matrix, so this must be taken into consideration. Specifically, the aluminum oxide may be contained in an amount of 10% by mass to 15% by mass based on the oxide composition. The content of aluminum oxide is preferably 11% by mass to 14% by mass, more preferably 12% by mass to 14% by mass based on the oxide composition. If the aluminum oxide content is less than 10% by mass, the plasticity component decreases, leading to deterioration of moldability, and if it exceeds 15% by mass, the crystallization of cristobalite crystals, which are stable at high temperatures, is suppressed, and firing deformation becomes rapidly large as the temperature rises after porcelainization.

[0046] Calcium oxide is mainly contained by adding bone ash, and it is preferable to add it so that the content is 10% by mass or more and 20% by mass or less based on the oxide standard composition. The content of calcium oxide is preferably 11% by mass or more and 18% by mass or less, more preferably 12% by mass or more and 17% by mass or less based on the oxide standard composition. Calcium oxide is mainly derived from bone ash, but it can also be added from wollastonite or lime. If the calcium oxide content is less than 10% by mass, the content of bone ash will inevitably decrease, the translucency as a porcelain material will decrease, and the characteristics of bone porcelain will be lost. If the calcium oxide content exceeds 20% by mass, the formation of a glass matrix will be insufficient due to the crystallization of anorthite crystals, and there is a high possibility that porcelain will not be formed.

[0047] The alkali metal oxide may be derived from feldspar, pottery stone, or sericite, and contributes to the formation of a glass matrix. The alkali metal oxide acts as a modifying oxide, cutting the structure of silicon dioxide and stabilizing the glass matrix, so this must be taken into consideration. Specifically, the alkali metal oxide may be contained in an amount of 0.3% by mass or more and 1.3% by mass or less based on the oxide-based composition. The content of the alkali metal oxide is preferably 0.4% by mass or more and 1.2% by mass or less, more preferably 0.5% by mass or more and 1.2% by mass or less based on the oxide-based composition. If the alkali metal oxide content is less than 0.3% by mass, the glass matrix is ​​insufficient and the porcelain is not porcelainized, and if it exceeds 1.3% by mass, the silicon dioxide is stable as a glass matrix, the crystallization of cristobalite crystals, which are stable at high temperatures, is suppressed, and the firing deformation becomes rapidly large as the temperature rises after porcelainization.

[0048] Diphosphorus pentoxide is mainly contained by adding bone ash or white rockite, and it is preferable that it is contained so that it is 14 mass% or more and 24 mass% or less on an oxide basis. The content of diphosphorus pentoxide is preferably 14 mass% or more and 22 mass% or less, more preferably 16 mass% or more and 20 mass% or less on an oxide basis. If diphosphorus pentoxide is less than 14 mass%, the bone ash content will inevitably decrease, the translucency as a porcelain material will decrease, and the characteristics of bone ash porcelain will be lost. If it exceeds 24 mass%, the ratio of silicon dioxide to diphosphorus pentoxide will decrease, so that the formation of a glass matrix will be insufficient and porcelainization will be unlikely.

[0049] In the above-mentioned ceramic composition, the basic framework is silicon dioxide, aluminum oxide, calcium oxide, alkali metal oxide, and diphosphorus pentoxide, and the compositions of the other components can be adjusted as needed. Therefore, in the claims of the present invention, the ceramic composition is specified by silicon dioxide, aluminum oxide, calcium oxide, alkali metal oxide, and diphosphorus pentoxide.

[0050] In the porcelain material used in the present invention, due to the above-mentioned composition, cristobalite, which is a silicon dioxide crystal that is stable at high temperatures, is crystallized from the glass matrix during firing and serves as an aggregate in place of molten α-quartz, so that the amount of firing deformation hardly increases even when the firing temperature is increased after porcelain formation.

[0051] The porcelain according to the present invention as described above is made of a main raw material composition with an appropriate compositional ratio, and it is possible to provide a porcelain in which the difference (rate of change) in the amount of firing deformation due to different temperature differences within a temperature zone during the firing process is suppressed.

[0052] Furthermore, according to the porcelain manufacturing method of the present invention, after porcelainization at a temperature of 1150°C or higher and 1280°C or lower, even if the firing temperature is increased by 50°C or more, the amount of firing deformation hardly increases, making it possible to manufacture porcelain products with stable shapes.

[0053] The present invention can provide a porcelain material containing 14% by mass or more of diphosphorus pentoxide (corresponding to 25% by mass or more of bone ash) and having low temperature dependency of firing deformation.The present invention can also provide a method for producing porcelain containing 14% by mass or more of diphosphorus pentoxide (corresponding to 25% by mass or more of bone ash) and not requiring the processes of double firing and glaze firing. EXAMPLES

[0054] The present invention will be described in more detail below with reference to examples and comparative examples according to the present invention.

[0055] The ceramic material according to the embodiment contains, on an oxide basis, 44% by mass to 60% by mass of silicon dioxide, 10% by mass to 15% by mass of aluminum oxide, 10% by mass to 20% by mass of calcium oxide, 0.3% by mass to 1.3% by mass of alkali metal oxide, and 14% by mass to 24% by mass of diphosphorus pentoxide, excluding unavoidable impurities, and is adjusted so that the total of these components accounts for 95% by mass or more of the total components. As shown in Table 1, the ceramic material is made from bone ash, clay, pottery stone, silica stone, silica, feldspar, lime, and wollastonite, and is a clay obtained by mixing these raw materials and adjusting the moisture content to 16% by mass to 25% by mass.

[0056] [Table 1]

[0057] The prepared clay is molded using a wheel-throwing machine or other molding methods, such as casting, casting, or press molding, and then dried. After drying, it is fired at temperatures between 1150 and 1330°C to obtain a porcelain product with no detectable water absorption.

[0058] According to the examples, when porcelain was fired at a first firing temperature T1 and a second firing temperature T2 that differed by 50°C within the firing temperature range of 1150°C or higher and 1330°C or lower (where T2-T1=50°C), porcelain was produced in which the rate of change in the amount of firing deformation was 40% or less.

[0059] In the examples, the characteristic that the firing deformation amount increases little or not at all even after porcelainization is utilized, and by performing sufficient firing after porcelainization, it is possible to obtain a glazed surface luster even with unglazed bisque firing. Thus, the present invention can provide a method for producing porcelain that does not require the bisque firing and bisque firing processes even though it contains 14% by mass or more of diphosphorus pentoxide (equivalent to 25% by mass or more of bone ash).

[0060] In the porcelain according to the present invention, after forming the clay base, underglaze painting or glazing may be performed before firing, but underglaze painting or glazing can also be performed after pre-firing at 700° C. to 1000° C. If the pre-firing temperature is too low, the strength of the base material becomes insufficient, making underglaze painting and glazing difficult, so it is desirable to adjust the pre-firing temperature as needed.

[0061] The firing temperature after glazing is between 1150℃ and 1330℃, and it is desirable to fire within the appropriate temperature range, which is about 50℃ wide for each clay composition. If the firing temperature is too low, the clay will absorb too much water and will not turn into porcelain. On the other hand, if the firing temperature is too high, the clay will warp and the yield will decrease. Example 1 Table 2 shows the sources of purchase of the raw materials listed in Table 1.

[0062] [Table 2]

[0063] Chemical analysis of the raw materials listed in Table 1 was performed using a fluorescent X-ray analyzer (ZSX PrimusII manufactured by Rigaku Corporation) with a calibration curve method using glass beads. Chemical analysis values ​​of the base material were calculated from the chemical analysis values ​​of the raw materials and their blending ratios and are shown in Table 3. Note that the silica in the table refers to the refining residue, mainly quartz, that is removed by elutriation from Amakusa pottery clay.

[0064] [Table 3]

[0065] A slurry was obtained by mixing 100 parts by mass of the raw materials shown in Table 1, 0.3 parts by mass of dispersant sodium silicate No. 3 (manufactured by Nippon Chemical Industry Co., Ltd.), and 30 parts by mass of water in a ball mill. The slurry was then molded into a plate-shaped sample measuring 20 mm x 7 mm x 125 mm by plaster mold casting to prepare a test piece, which was then dried. The plate-shaped sample 1 thus prepared was placed on a sample support table 2 with a span of 100 mm as shown in Figure 1, and fired in a kiln at a temperature of 1150°C to 1330°C to prepare a test piece.

[0066] The test pieces thus prepared were used for testing according to the following test methods, and the results are shown in Table 4.

[0067] 1. Confirmation of porcelain After firing, the test pieces were immersed in the fuchsin solution for one hour, then removed and washed with water. If the absorption of the fuchsin solution into the base material was not confirmed, it was judged to have been porcelainized, and the results are shown in Table 3.

[0068] 2. Amount and rate of deformation during firing The maximum change in the firing deformation 3 shown in Figure 2 was measured and is shown in Table 4. The firing deformation 3 is defined as the distance between the horizontal plane connecting the two supports 5 that contact and support the test piece on the sample support table 2 and the bottom surface of the test piece. D1 = the amount of firing deformation when firing at the first firing temperature T1 between 1150°C and 1330°C D2 = the amount of firing deformation when firing at the second firing temperature T2 between 1150°C and 1330°C However, T2-T1=50℃ The rate of change in firing deformation was calculated from the above D1 and D2 using the following formula and is shown in Table 4. Rate of change in firing deformation = {(D2-D1) / D1} x 100

[0069] [Table 4]

[0070] In this example, the firing deformation amount and the rate of change in firing deformation amount were evaluated by the above-mentioned method. Note that, at present, there are no JIS standards or industry standards in the ceramic industry for the evaluation of firing deformation amount and the rate of change in firing deformation amount. 3. Identification of Crystalline Phases The results were confirmed using an X-ray diffraction apparatus (SmartLab manufactured by Rigaku). The value obtained by dividing the first peak height of cristobalite at about 2θ = 21.7 by the second peak height of α-quartz at about 2θ = 20.7 is shown as the C1 / Q2 peak height ratio in Table 4. Note that for Comparative Example 1 and Comparative Example 2, the C1 / Q2 peak height ratio is not shown because the cristobalite peak could not be confirmed.

[0071] As shown in Table 4, the rate of change in firing deformation in Example 1 was 2.3% within a 50°C range between 1200°C (first firing temperature T1) and 1250°C (second firing temperature T2).

[0072] As shown in FIG. 3, in the X-ray diffraction pattern of the ceramic material of Example 1 fired at 1200° C., the first peak of cristobalite near 2θ=21.7° was higher than the second peak of α-quartz near 2θ=20.7°.

[0073] As shown in Figure 4, the peak of cristobalite in the X-ray diffraction pattern of the porcelain material of Example 1 fired at a temperature of 1250°C is higher than the peak of cristobalite fired at a temperature of 1200°C shown in Figure 3. On the other hand, the peak of α-quartz is lower than the peak of the porcelain material fired at a temperature of 1200°C. It was confirmed that cristobalite crystallized in place of molten α-quartz and acted as an aggregate to prevent and reduce firing deformation. (Examples 2 to 16) Except for changing the compounding conditions of Example 1 to those described in each Example in Table 1, samples prepared in the same manner as in Example 1 were measured in the same manner as in Example 1. In each Example, the rate of change in firing deformation was 0.0% or more and 38.6% or less in the firing temperature range of 50°C (the range between the first firing temperature T1 and the second firing temperature T2) in the firing temperature range in which porcelain was produced.

[0074] As described above, it can be seen that the rate of change in firing deformation defined above is 40% or less according to the method for producing porcelain according to the present invention. Thus, the present invention can provide a porcelain material that contains 14% by mass or more of diphosphorus pentoxide (corresponding to 25% by mass or more of bone ash) yet has a rate of change in firing deformation of 40% or less and has low temperature dependency of firing deformation.

[0075] In each example, at the sintering temperature, the first cristobalite peak near 2θ=21.7° was higher than the second α-quartz peak near 2θ=20.7° in the X-ray diffraction pattern. In the table, the C1 / Q2 peak ratio of Example 4, which was fired at a temperature of 1150°C, was 1.1, and in this example as well, the first cristobalite peak was higher than the second α-quartz peak.

[0076] In addition, in each example, when the firing temperature increased from the first firing temperature T1 to the second firing temperature T2, the peak intensity indicating cristobalite increased in the X-ray diffraction pattern, and the peak intensity of α-quartz relatively decreased, thereby increasing the C1 / Q2 peak ratio. Comparative Example 1 Comparative Example 1 is a typical bone china within the blending range described in Patent Document 3.

[0077] A sample was prepared in the same manner as in Example 1, except that the compounding conditions in Example 1 were changed to those in Comparative Example 1 in Table 1. The sample was fired at a firing temperature of 50°C between 1200°C and 1250°C, as indicated in Patent Document 3. The firing deformation D1 of Comparative Example 1 fired at 1200°C was 8.5mm, but the firing deformation of Comparative Example 1 fired at 1250°C was large and the sample was in complete contact with the bottom of the sample support 2. Since the firing deformation does not increase after contact with the sample support 2, the rate of change in firing deformation cannot be measured accurately, but the firing deformation D2 at the time of contact was 19.0mm, and the rate of change in firing deformation in the contact state was 123.5%. It was confirmed that Comparative Example 1 showed a large rate of change in firing deformation of 123.5% or more. Strict temperature control is required to manufacture porcelain using the material of Comparative Example 1 in the process of bisque firing, glaze application, and main firing.

[0078] Figure 5 shows an X-ray diffraction pattern of the porcelain material of Comparative Example 1 fired at 1200°C. In the comparative example, the crystalline phase that becomes the aggregate only has low peaks of α-quartz at around 2θ=20.7° and 2θ=27°. Figure 6 shows an X-ray diffraction pattern of the porcelain material of Comparative Example 1 fired at 1250°C. Compared to the porcelain material of Comparative Example 1 fired at 1200°C, the α-quartz peak has rapidly decreased, and no aggregate replacing α-quartz has been observed. It can be seen that the firing deformation has rapidly increased due to the decrease in aggregate that prevents softening deformation. Comparative Example 2 Comparative Example 2 is a typical mass-produced porcelain that is subjected to the steps of bisque firing, glazing, and final firing.

[0079] A sample was prepared in the same manner as in Example 1, except that the compounding conditions in Example 1 were changed to those in Comparative Example 2 in Table 1. The sample was measured in the same manner as in Example 1, and the amount of firing deformation when fired at 1290°C in Comparative Example 2 was 7.5 mm. Also, the amount of firing deformation when fired at 1320°C was 11.8 mm. The rate of change in firing deformation was 57% within 30°C of the firing temperature range of 1290°C to 1320°C for porcelainization. For Comparative Example 2, the rate of change in firing deformation was verified based on a temperature difference of 30°C.

[0080] Compared with Comparative Example 2, the ceramic material of the present invention has a smaller rate of change in firing deformation over a wider temperature range, indicating that it can be manufactured stably without going through the process of underglaze firing.

[0081] As described above, the porcelain according to the present invention is made of a main raw material composition with an appropriate compositional ratio, and it is possible to provide a porcelain in which the difference (rate of change) in the amount of firing deformation due to different temperature differences within a temperature zone during the firing process is suppressed.

[0082] Furthermore, according to the porcelain manufacturing method of the present invention, after porcelainization at a temperature of 1150°C or higher and 1280°C or lower, even if the firing temperature is increased by 50°C or more, the amount of firing deformation hardly increases, making it possible to manufacture porcelain products with stable shapes.

[0083] The present invention also provides a porcelain material that contains 25% or more bone ash and has low temperature dependence of firing deformation.The present invention also provides a method for producing porcelain that contains 25% or more bone ash and does not require the processes of double firing and glaze firing. [Explanation of symbols]

[0084] 1. Plate-shaped sample 2. Sample support table 3. Firing deformation amount 5...Fulcrum

Claims

1. A ceramic made from a main raw material composition containing, on an oxide basis, excluding unavoidable impurities, 44% by mass or more and 60% by mass or less of silicon dioxide, 10% by mass or more and 15% by mass or less of aluminum oxide, 10% by mass or more and 20% by mass or less of calcium oxide, 0.3% by mass or more and 1.3% by mass or less of alkali metal oxide, and 14% by mass or more and 24% by mass or less of diphosphorus pentoxide.

2. The ceramic according to claim 1 , further comprising a secondary raw material composition other than the main raw material composition.

3. The ceramic according to claim 2, wherein the main raw material composition is 95% by mass or more.

4. 2. The porcelain of claim 1 having cristobalite as a crystalline phase.

5. 5. The ceramic according to claim 4, wherein the first peak of cristobalite at 2θ=21.7° in an X-ray diffraction pattern is greater than the second peak of α-quartz at 2θ=20.7°.

6. 2. The ceramic according to claim 1, wherein the main raw material composition contains feldspar in an amount of less than 7 mass%.

7. a preparation step of preparing a clay made of a main raw material composition containing, on an oxide basis, excluding unavoidable impurities, 44% by mass or more and 60% by mass or less of silicon dioxide, 10% by mass or more and 15% by mass or less of aluminum oxide, 10% by mass or more and 20% by mass or less of calcium oxide, 0.3% by mass or more and 1.3% by mass or less of alkali metal oxide, and 14% by mass or more and 24% by mass or less of diphosphorus pentoxide; A molding process of molding the china clay adjusted in the adjustment process into a molded body; A firing step of firing the compact formed in the forming step at 1150°C or higher and 1330°C or lower.

8. The method for producing ceramics according to claim 7, further comprising a secondary raw material composition other than the main raw material composition.

9. The method for producing ceramics according to claim 8, wherein the main raw material composition is 95 mass% or more.

10. The method for producing ceramics according to claim 7, wherein the ratio of feldspar in the raw materials of the main raw material composition is less than 7 mass%.

11. First firing temperature T in the range of 1150° C. to 1330° C. 1 The amount of deformation when fired at D 1 year, Second firing temperature T in the range of 1150° C. to 1330° C. 2 The amount of deformation when fired at D 2 (However, T 2 -T 1 = 50 ° C.), {(D 2 -D 1 ) / D 1 8. The method for producing ceramics according to claim 7, wherein the rate of change in firing deformation calculated by the formula (1) is 40[%] or less.

Citation Information

Patent Citations

  • Manufacture of bone chinas

    JP1978052514A

  • Method for producing white ceramic and glaze suitable therefor

    JP2011121850A

  • Fish bone ash for bone china and method for producing the same

    JP2016079074A